Gratitude and life satisfaction among Filipino adolescents: The mediating role of meaning in life - Datu, Jesus Alfonso D. (Animo Repository, 2015)
The current research assesses the mediating effects of meaning in life on the relationship between gratitude and life satisfaction. A sample of Filipino college students (N = 409) in a private sectarian university completed the Gratitude Questionnaire Six-Item Form (GQ-6), Meaning in Life Questionnaire (MLQ), and Satisfaction with Life Scale (SWLS). Findings revealed that both gratitude and presence of meaning in life were positively associated with life satisfaction. Interestingly, search for meaning in life was negatively correlated with presence of meaning in life. Hierarchical multiple regression analyses showed that presence of meaning in life partially mediated the relationship between gratitude and subjective well-being. Implications of the findings on the development of positive psychological interventions in the context of counseling are discussed. © 2015, Springer Science+Business Media New York.